If Margaret Mead was a Librarian: Observation and Visitor Experience at Libraries in Russia and the Baltic States. Issue 1 (2nd January 2017) - Reddacliff, Anne
Abstract: Drawing on qualitative research methods and design thinking, this paper reports on a project that aimed to gain a rich understanding of visitor experience at libraries in Russia and the Baltic States. The research combined methodologies from the disciplines of library and information science and social sciences. A discussion about ethnology and design thinking outlines the relevance of these approaches and application in the library and information science field. Unobtrusive observation, field notes and photographs were used to record the researcher's experience and word clouds were created from these data to illustrate the emotions and sensations of visitor experience.